Effect Of E-Learning On Theoretical-Practical Lessons Training To Produce Learning Programs - Golbabaei, Maryam (The Turkish Online Journal of Design Art and Communication, 2016)
The present research aims on effect of e-learning and traditional learning on training theoretical-practical lessons to produce curriculum programs in McS students of technology. Research hypotheses were proposed named as e-learning in training curriculum contents to produce training programs is more effective than traditional learning. Statistical population includes McS students and sampling include accessible sample by 50 students in 2 classes in which 25 students were test and control groups. The results by t-test showed that traditional training method act a little more successful.
Keywords: e-learning; traditional learning; training; curriculum programs production